Green strategy for gaining competitive advantage in pharmacy: Exploring the role of green and social innovation - Budi Nur Siswanto; Irayanti Adriant; Rizqi Permana Sari; Agus Rahayu (Asian Management and Business Review)
Green strategy practices have become a major concern for many companies seeking to achieve competitive advantage. This study aims to explore the influence of green strategy on social innovation and green innovation and its impact on competitive advantage in pharmaceutical companies. A sample of 53 respondents consisting of the private sector and state-owned enterprises were selected in this study and then analyzed using a structural equation model (SEM-PLS). The results showed that the implementation of green strategy as a whole positively affects social innovation, green innovation, and competitive advantage. In addition, the role of mediation of social innovation and green innovation can strengthen the influence of green strategy on competitive advantage by increasing the company’s ability to innovate sustainably, as well as responding to increasingly environmentally conscious needs. The findings of the present study contribute to the literature, especially in strategic management, by offering notions of how to achieve competitive advantage. It also provides practical implications for companies to enable them to implement steps in environmentally friendly business practices.